A fluctuation theorem for moderately interacting diffusion processes - Oelschläger, Karl (Probability theory and related fields, 1987)
We study the asymptotic behaviour of the fluctuations of the empirical processes of the second example of “moderately” interacting diffusion processes of [3] and show that in the limit, as the number of different processes tends to infinity, these fluctuations behave gaussian.